Preparation and Characterization of Novel Schiff Base Obtained from Dialdehyde Galactomannan and Aniline - Umamaheswari, G.; V. Kanth, Swarna; Umapathy, M.J. (Asian Journal of Chemistry, 2012)
Guar gum is a straight chain galactomannan, obtained from the endosperm of leguminaceae plant, Cyamposis tetragonalobus. The modification of guar gum is carried out by periodate oxidation, it specifically cleaves the vicinal glycols in galactomannan to form dialdehyde galactomannan. The product was then reacted with aniline to form yellow coloured Schiff base characterized by the shift in UV-Visible spectroscopy and the formation of aldehydic and imine functional group was endorsed by FTIR. Thermal studies of guar gum, dialdehyde galactomannan and imine show decrease in decomposition temperature from the guar gum to imine. This could be explained due to the cleavage of glycosidic linkage.